Islamic radicalism that never was: Islamic discourse as an extension of the elite's quest for legitimation. Azerbaijan in focus. Issue 2 (July 2019) - Ismayilov, Murad
Not unlike the global dynamics and the developments in the rest of Central Eurasia, Islamic discourse in Azerbaijan over the past two decades has not reflected the micro-level shifts in the country's social-cultural landscape. Rather, it has been formed and evolved as a collateral product of the elite's tactical pursuit of legitimation across domestic and international planes of power. Grounded in its quest for tactical and strategic survival, the elite's pursuit of Western (and broader international) recognition, in particular, has stood at the core of the elite's policies toward Islam and molded the confines of state-promoted Islamic discourse. The regime's overall strategy has been to continuously reinforce the representation of Islam as an imminent danger to the stability and secular nature of Azerbaijani statehood, while positioning itself—in the eyes of both the "liberal, " "democratic" West and the secularized population at home—as the sole force capable of staving off the Islamic threat. At that, the narrative of Islamic radicalism in Azerbaijan has centered around three principal dynamics: the regime's anti-hijab policies, the regime's policies toward the settlement of Nardaran in Baku's suburbs, and the activities of the Islamic Party of Azerbaijan (IPA). This article provides a closer look at all three to expose the elite's intention of using these as their primary trigger mechanisms and reference points in the quest for Western—and secular domestic—legitimation and, as such, the pursuit of the negative representation of Islam as a threat to secularity and modern statehood.